Pensonic Holdings Berhad / Nurul Natasya Che Abdul Halim - Abdul Halim, Nurul Natasya Che (2020)
Pensonic Holdings Berhad is a company that produces variety types of household appliance products. Pensonic Holdings Berhad is a publicly traded company founded by Dato' Sri Chew Weng Khak in 1994. It is located at Penang, Malaysia. One of the products produce by Pensonic company is Pensonic iron. Iron is an electric appliance that help to diminish crease at clothes. There are two types of iron produced by this company that are dry iron and steam iron. The objectives of this study are to analyse the problems that Pensonic Holdings Berhad Company faced and provide better solutions to overcome the problems and to suggest a recommendation to the company in order to improve their company in the future. After doing company analysis, there are several problems founded about the Pensonic Steam Iron. The problems are the iron use the manual technology, the problem of water dripping when using the steam iron and the iron cannot be used to wet clothes and heavy fabrics. Therefore, this study comes out with three alternatives. The first alternative is producing an automatic steam closet. The closet uses the steam system where can help in drying clothes and diminish wrinkle just by hanging clothes in it. The second alternative is changing the current type of soleplate which from Teflon into a stainless-steel type of soleplate. The last alternative is adding an anti-drip measure into the steam iron. The anti-drip measures help the problem of water dripping. Thus, this study come out with a recommendation to choose one of the alternatives. This study suggested to choose producing Automatic Steam Closet. This is because this closet can solve almost all the problems faces by the existing steam iron.